HOMONYMS COMPARISONAL ANALYSIS IN THE ENGLISH AND RUSSIAN LANGUAGES - Bobonazarova, Muxlisa Yomg‘ir qizi (Educational Research in Universal Sciences, 2023)
This article discusses about the interlanguage homonyms in media texts and Cultural aspects of homonyms. It includes, as a demand ABSTRACT, keywords, introduction, main part, conclusion and reference.